Um estudo sobre crescimento de nanofios de fosfeto de índio e algumas de suas propriedades - Kamimura, Hanay (2016)
This work presents the development of an experimental apparatus and a route for the growth of InP nanowires whose general characteristics and properties made them suitable for the construction of electronic devices. Among theses characteristics, one may cite: desired dimensions, uniformity, quantity and composition. The synthesis system allowed the growth of a large amount of InP nanowires with diameter distributed around values smaller than 80 nm, grown in different substrates, covering them with a dense and uniform layer. Most important, all this in a reproducible way. The structural and morphological analyses, which resulted in the above described characteristics also allowed the observation of a amorphous/polycrystalline layer around the mono crystalline nucleus of the nanowires. Afterwards, the optoelectronic properties of the samples were studied. For this purpose, three types of devices were fabricated: single nanowire based devica, built using photolitography; nanowires network based device built from direct evaporation of contacts over the nanowires layer and from the growth of nanowires over pre defined contacts. The electronic transport mechanism was investigated by temperature dependent resistance measurements, obtaining the same dominant mechanism of hopping in all three types of device. This result indicates that the effect of the disorder attributed to the amorphous/polycrystalline layer and its interface to the monocrystalline nucleus was a critical factor to the determination of the sample’s properties. In order to complement and confirm the obtained results, other experiments were carried out: thermally stimulated current, showing additional energy levels inside the band gap, indicated in literature as levels originated from structural disorder; photo luminescence measurements, presenting a strong potential fluctuation due to localized states and photoconductivity, obtaining a sub linear dependence with the power excitation, typically observed in material with the presence of carrier traps. In this manner, the influence of localized states due to structural disorder was confirmed as the maind factor to the samples behaviour for both electronic and optical properties.